ANIMAL SYMBOLISM IN INDIAN AMERICAN POETRY - Hassan, Adel El-Sayed; Sadek, Sayed (European Scientific Journal, ESJ, 2015)
This study attempts to give a brief account of the employment of animals as symbols by such eminent Native American women poets as Leslie Marmon Silko, Joy Harjo and Linda Hogan. The animals include those whose images appear with high frequency in Native American culture and literature such as the bear, the wolf, the horse, the turtle, and others. The article analyses and compares the different metaphors of different animals as portrayed by the poets under study in order to relate these symbols to the cultural and psychological meanings in their poems. It also marks the points of difference between the use of animal images by European and Native American poets. This will be conducted by employing eco-criticism, a school of criticism which pays due attention to the equality between animals and humans. The study concludes that the Native American poets believe in the kinship with all creatures and dream of restoring the golden days when all creatures received equal appreciation before the coming of the colonizers.